SEASONAL OCCURRENCE OF PENAEUS SEMISULCATUS DE HAAN, PANULIRUS POLYPHAGUS (HERBST) AND PORTUNUS (P.) PELAGICUS (LINN.) IN THE COCHIN BACKWATER - Rao, P Vedavyasa; Kathirvel, M (Indian Journal of Fisheries, 2011)
Distribution al1d abundance of Penaells selllislilcallls de Haan and Porlll/llls (PorIUl/lls)pelagiclis (Linnaeus) in relation to salinity and temperature variations in Cochin backwaterhave been studied. These species disappear from this environment in July, whenthe salinity and the temperature decrease and reappear again in November-Decemberwhen the values of these factors increase. As compared to the related species of commercialpenaeid prawns and portunid crabs occurring in the backwaters, these speciesto be less euryhaline. The appear interesting phenomenon of occurrence of post-larvalstages of the truly marine spiny lobster, POllldims polypflaglls (Herbst) in these estuarineand juvenile waters is also reported here for the first time.